Ensayo metodológico para la valoración estética del paisaje. Aplicación en Muntanyes d’Ordal (Barcelona) - Serrano Giné, David (Geographicalia, 2015)
Among landscape studies, one of the aspects of most interest refers to techniques and methods to consider values of aesthetic type. By general rule, these exercises are used to be considered subjective and little systematic, fact that can reduce its interest and applicability. From an indirect methodology based on the weighed aggregation of elements, an aesthetic valuation of landscape is developed at Muntanyes d’Ordal, a periurban area near the city of Barcelona.